(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2018)
The novel is the closest gender to reality, although the novel is not devoid of fiction of its author , but realism is the predominant characteristic of it, especially the Iraqi novel, which has been characterized since its existence with this feature, but the reality means within represents things by the closest in the world of reality this is also influenced by the artist’s inclinations and way of his understanding and angle of view we are in this research we are with two novels approaching without a literal photographic match with that reality which is the obvious context in this text and its baseline reference for it. We found a lot of common and converging reasons between these two novels, especially the intentional categories of their character , as well as tracking the recent history of the presence of Christians in Iraq. The coexistence of the sons of this community before the many changes and the transformations that took place after 2003 and the fact that many of sons of this segment were forced to leave the country either willingly or obliged to do that.